Getaran Akibat Gangguan Secara Alami - Soeharsono .; Radite Praeko Agus Setiawan (PERTETA, 2008)
This paper discusses the phenomenon of self-excited vibration in some physical model including its applications in some different engineering field. The referred physical model include the impact damper and its application for damping the vibration of shear building, chatter phenomenon on machine tools, ride comfort on agricultural machinery and stick-slip phenomenon and its benefit on vibration subsoiler. It is intended that this paper could provide a global overview on phenomenon-of self-excited vibration. Keywords: self-excited, vibration, stick-slip, subsoile Diterima: 03 Januari 2008; Disetujui: 12 Mei 2008